Preparing Health and Physical Education Teachers to Become Trauma Invested: Introduction to Feature Series. Issue 9 (21st November 2020) - L. Walton-Fisette, Jennifer; Ellison, Douglas
Abstract : The purpose of the feature series is to prepare health and physical education teachers, both at the K-12 and higher education levels, on how to become knowledgeable about trauma, toxic stress, Adverse Childhood Experiences (ACEs), the warning signs and symptoms, and how to minimize potential triggers by engaging in trauma-invested practices. This is exceedingly important at a time when mental health issues and social emotional learning is at the forefront of education discussions. Currently, licensed teachers are not prepared to educate, assist, and support students who are dealing with extensive trauma, which significantly influences their ability to learn. Our hope through this feature series is to provide professional development to K-12 health and physical education teachers and higher education health and physical educators. Although there is some quantitative research at the elementary and secondary levels on trauma, ACEs, and student learning, there hasn't been any research or much focus specific to health and physical education. Since social emotional learning is also a salient focus, we want to be sure to integrate this content along with trauma-invested practices. Furthermore, looking at both trauma and social emotional learning by also addressing the socially unjust practices that may enhance these issues is needed.